Pengaruh SBSN dan SUN terhadap Pertumbuhan Ekonomi Indonesia Tahun 2015–2024 - AZIS R, ABDUL; ANDRIANI, NINI; UTAMI, AYU PUTRI; M, WISRA; HAMZAH KARIM, SITTI AMINAH (Journal of Management and Leadership, 2025)
This study aims to examine the effect of Government Sharia Securities (SBSN) and Government Debt Securities (SUN) on Indonesia's economic growth as measured by Gross Domestic Product (GDP). A quantitative approach with a positivistic paradigm is used in this study, with quarterly data from 2015 to 2024 processed using the Partial Least Squares - Structural Equation Modeling (PLS-SEM) analysis technique. The results of the study indicate that SBSN has a positive and significant effect on GDP, indicating that increasing SBSN issuance can drive Indonesia's economic growth. On the other hand, SUN does not show a significant effect on GDP, indicating that the use of SUN is more widely used for short-term and consumptive financing, not for financing productive projects that can increase national output. These findings provide theoretical contributions related to the role of state financing instruments in the economy and suggest that SBSN issuance policies need to be maximized to support sustainable development. In addition, evaluation of the use of SUN is also needed to direct more productive fund allocations, in order to support inclusive and sustainable economic growth.